Measuring the negative externalities of a private leisure activity: hooligans and pickpockets around the stadium - Montolio, Daniel (Journal of economic geography, 2000)
Given the recent increase observed in crime related to football matches, we determine the extent to which this private leisure activity is responsible for negative crime externalities. We conduct an Exploratory Spatial Data Analysis and spatial regressions at the census tract level drawing on data for the matches played by Football Club Barcelona and geocoded crime data for the city of Barcelona (Spain); focusing on thefts (mainly pick pocketing) and assaults (interpersonal violence or hooliganism). We find an increase in the number of thefts across the whole city but, especially, in those census tracts within a 700-m radius of the stadium. These results are confirmed by the low number of crimes committed during away matches in the census tracts around the stadium. A similar spatial pattern is found for assaults. Our results provide evidence of a displacement effect of violent supporters (hooligans) towards the stadium on football days